Fanconi's Anemia Effect or Sickle Cell Anemia Effect: That is the Question. (August 2015) - Unal, Sule; Chui, David H.K.; Gumruk, Fatma
Abstract A 16-year-old boy who was diagnosed to have sickle cell anemia was referred to our center. The parental consanguinity, growth retardation and dysmorphic features prompted a search for possible Fanconi's Anemia (FA). The diepoxybutane (DEB) test was positive, confirming FA. The interaction of both diseases might account for his relatively mild phenotype in terms of both sickle cell anemia (or Hb S, HBB: c.20A > T) and FA. The high Hb F level that might be related to concomitant FA, may have caused a milder phenotype of sickle cell anemia, whereas nitric oxide (NO) depletion as a consequence of sickle cell anemia, may have caused a delay in the bone marrow failure of FA.